Types of Passive Voice Found in The Novel Say You’re Sorry by Michael Robothom - Giri Ratih, Luh Made (Humanis; Vol 22 No 3 (2018), 2018)
This undergraduate thesis entitled Types of Passive Construction in the Novel Say You’re Sorry by Michael Robotham is aimed at analyzing the types of passive voice found in the novel and figuring out which one among them is the most dominant used in the novel. The data source of this study was taken from Michael Robotham’s Say You’re Sorry which was published by Sphere in 2012. This study is a descriptive qualitative and quantitative research and the method used to collect the data was the documentation method using the note taking technique. The result of this study shows that there are only three types of passive voice found in the novel: be passive, get passive, and bare passive. From 219 passive sentences taken from the novel, 207 of them is be passive with the percentages of 95% while there are only 7 sentences of get passive with percentage of 3% and 5 sentences of bare passive type with the percentage of only 2%.